2017
DOI: 10.1055/s-0043-117773
|View full text |Cite
|
Sign up to set email alerts
|

Auf dem Weg zu kultursensitiven Patienteninformationsmaterialien: Ergebnisse einer Fokusgruppenuntersuchung

Abstract: Although the identified categories were relevant for all or for the majority of migrant groups, for most categories specific cultural aspects were discovered. These findings show the importance of a culture sensitive adaptation of PIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Possible reasons for this are cultural and age-related attitudes and preferences vis-à-vis the doctor-patient relationship. Different studies in German found a rather paternalistically determined perspective on this relationship in patients with a family background of immigration from Turkey (26) and in Russian-speaking immigrants (27,28). It is plausible that redistribution of MT from physicians to MPA is regarded more critically among those who have internalized the idea of a paternalistic doctor-patient relationship to a greater extent.…”
Section: Discussionmentioning
confidence: 98%
“…Possible reasons for this are cultural and age-related attitudes and preferences vis-à-vis the doctor-patient relationship. Different studies in German found a rather paternalistically determined perspective on this relationship in patients with a family background of immigration from Turkey (26) and in Russian-speaking immigrants (27,28). It is plausible that redistribution of MT from physicians to MPA is regarded more critically among those who have internalized the idea of a paternalistic doctor-patient relationship to a greater extent.…”
Section: Discussionmentioning
confidence: 98%